Zarządzanie publiczne a wyzwania polityki innowacyjnej w Polsce - Kwieciński, Leszek (Public Management and Challenges of Innovation Policy in Poland, 2008)
This article shows the main institutional and system's elements which concern the innovation policy in Poland. The author focuses on the questions which are related to the transformation of public roles like: citizen/stakeholder, network, partnership, leadership, in the aspects of public management. At the end of the paper it is highlighted that Poland needs more time for the proper implementation of this new public policy and the author summarizes the main problems of the Polish innovation policy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 177-184